Antibacterial activity of silver nanoparticles: A surface science insight. Issue 3 (June 2015) - Le Ouay, Benjamin; Stellacci, Francesco
Graphical abstract: Highlights: Recent results indicate the crucial role of Ag + in the action mechanism of Ag 0 nanoparticles. Ag + is released from metallic nanoparticles through oxidative dissolution, notably due to atmospheric O2 . Ag + release is highly dependent on the surface chemistry of the nanoparticles. Among other phenomena, Ag nanoparticles activity is very sensitive to the presence of some anions, that modify the dissolution behavior. Summary: Silver nanoparticles constitute a very promising approach for the development of new antimicrobial systems. Nanoparticulate objects can bring significant improvements in the antibacterial activity of this element, through specific effect such as an adsorption at bacterial surfaces. However, the mechanism of action is essentially driven by the oxidative dissolution of the nanoparticles, as indicated by recent direct observations. The role of Ag + release in the action mechanism was also indirectly observed in numerous studies, and explains the sensitivity of the antimicrobial activity to the presence of some chemical species, notably halides and sulfides which form insoluble salts with Ag + . As such, surface properties of Ag nanoparticles have a crucial impact on their potency, as they influence both physical (aggregation, affinity for bacterial membrane, etc. ) and chemical (dissolution, passivation, etc. ) phenomena. Here, we review the main parameters that will affect the surface state of Ag NPs and their influence on antimicrobial efficacy. We also provide an analysis of several works on Ag NPs activity, observed through the scope of an oxidative Ag + release.